The high-mountain cryosphere environmental changes and human risks - Huggel, Christian; Carey, Mark; Clague, John J. 1946- (Cambridge Univ. Press, 2015)
This edited volume, showcasing cutting-edge research, addresses two primary questions - what are the main drivers of change in high-mountains and what are the risks implied by these changes? From a physical perspective, it examines the complex interplay between climate and the high-mountain cryosphere, with further chapters covering tectonics, volcano-ice interactions, hydrology, slope stability, erosion, ecosystems, and glacier- and snow-related hazards. Societal dimensions, both global and local, of high-mountain cryospheric change are also explored. The book offers unique perspectives on high-mountain cultures, livelihoods, governance and natural resources management, focusing on how global change influences societies and how people respond to climate-induced cryospheric changes. An invaluable reference for researchers and professionals in cryospheric science, geomorphology, climatology, environmental studies and human geography, this volume will also be of interest to practitioners working in global change and risk, including NGOs and policy advisors
Keywords: Klimaänderung; Glacial landforms; Permafrost; Climatic changes; Global warming; Kryosphäre; Umweltfaktor; Hochgebirge; Aufsatzsammlung